A multilevel diakoptics algorithm for large scale networks - Yu, Fu-Chaw; Wu, Yan-Pei (Journal of the Chinese Institute of Engineers, 1988)
Diakoptics methods for large scale networks have been widely studied and applied over the last decade. Most of the applications used single level diakoptics of a network into subnetworks. The previous works treat networks either by node tearing or by connecting all the tie lines at the same time [1, 6, 9, 12, 14]. In this paper, tearing is applied to hierarchically described networks and a new algorithm based on Gaussian elimination is presented. Using a multilevel algorithm, the new method tears a network into multilevels and always joins two subnetworks by a set of the lines recursively. Finally, the macromodel (solution model) of a large scale network is presented.